Lean thinking for emerging healthcare leaders : how to develop yourself and implement process improvements - Orelio, Arnout (Healthcare management collection., 2020)
This book aims to solve the issues in modern day healthcare by handing over the reins of the improvement process to healthcare professionals. Putting those who are doing the work and are closest to the actual situation in the lead. The purpose of this book is to help you understand how to develop yourself and your leadership in such a way that will best benefit your team and your patients. This includes change management practices that will help to build commitment with your team members, colleagues, management, patients, and other stakeholders.